2022
DOI: 10.3390/foods11142090
|View full text |Cite
|
Sign up to set email alerts
|

Research Update on the Impact of Lactic Acid Bacteria on the Substance Metabolism, Flavor, and Quality Characteristics of Fermented Meat Products

Abstract: This paper reviews the effects of domestic and foreign influences on the substance metabolism pathways and the flavor and flora of LAB in fermented meat products to provide a new theoretical basis for developing new products for the industrial application of lactic acid bacteria (LAB) in fermented meat products. LAB are extensively used among commonly fermented ingredients, such as fermented meat products and yogurt. As fermenting agents, LAB metabolize proteins, lipids, and glycogen in meat products through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 101 publications
1
18
0
Order By: Relevance
“…[ 22 ]. Even before scientific observations were carried out, spontaneous microflora, including yeasts [ 23 ] and molds, were unwillingly used to obtain and preserve fermented meat products [ 24 , 25 ], thus leading these microorganisms to play a critical role in modern food production and food safety [ 3 , 26 ]. LAB and coagulase-negative cocci play the main role in processes related to meat fermentation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 22 ]. Even before scientific observations were carried out, spontaneous microflora, including yeasts [ 23 ] and molds, were unwillingly used to obtain and preserve fermented meat products [ 24 , 25 ], thus leading these microorganisms to play a critical role in modern food production and food safety [ 3 , 26 ]. LAB and coagulase-negative cocci play the main role in processes related to meat fermentation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that staphylococci are to be found in the outer layers of fermented salami-type products as a result of higher oxygen concentrations [ 31 ], whereas LAB proliferates in the low oxygen parts (core) [ 27 ]. The preserving effect (the inhibition of pathogen growth) of beneficial microorganisms in fermented meat products is due to the combination of sugar metabolism, organic acid synthesis, and the acidification of the substrate [ 25 , 28 ]. This leads to the lowering of pH values to optimum safety levels (pH < 5.2), which is usually achieved 48–72 h after incubation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An accumulation of studies has reported that the unique flavor of fermented meat products is not only related to the enzymes in the raw meat but also closely related to the various micro-organisms that are involved in the natural fermentation process [ 6 ]. Micro-organisms affect the flavor of fermented meat products by participating in (1) the hydrolysis and self-oxidation of lipids in the raw meat [ 7 , 8 ], (2) the hydrolysis of proteins and carbohydrates [ 9 , 10 , 11 ], (3) the formation of amino acid and peptide derivatives with flavor activity [ 12 ], and (4) the formation of volatile organic compounds (VOCs) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, LAB are widely used in the fermentation of meat products and the fermentation systems of other raw materials. Their growth can regulate the protein degradation and oxidation in fermented meat products to a certain extent, add characteristic flavors to the products and improve the safety of fermented food [13,14]. In addition to LAB, Staphylococcus demonstrated excellent protein degradation ability.…”
mentioning
confidence: 99%